Nurses' human dignity in education and practice: An integrated literature review - Akram Parandeh; Morteza Khaghanizade; Eesa Mohammadi; Jamileh Mokhtari-Nouri (Wolters Kluwer Medknow Publications, 2016)
Background: Human dignity, as a fundamental human right and a moral obligation, has been emphasized in different fields of nursing. The aim of the present integrative review was to explore the nature of nurses' human dignity in educational and clinical settings. Materials and Methods: A literature review was conducted on quantitative and qualitative research papers in English and Persian using the PubMed, ProQuest, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Google Scholar, SID, and Irandoc databases from the year 2000 to 2013. Keywords for the search included dignity, nursing, faculty, nurse clinicians, nursing student, and humanism. In total, 12 research papers met the inclusion criteria for the integrative review. Results: From this review, four key themes emerged. The themes consisted of concept of human dignity (it was as an expression of the professional value in nursing settings), factors affecting human dignity (including respect, communication, autonomy and power, competency and ability, structure of the workplace, and value-based education), dimensions of human dignity (including intrinsic and professional domains), and consequences of human dignity [positive (individual and professional growth and caring professional behavior) and negative (loss of motivation, intention to leave the profession, and non-professional image of nursing in the minds of people)]. Conclusions: The small number of studies found for the review indicates the need for further research in the field of nurses' dignity. Recognizing nurses' dignity can help to improve the nursing practice and provide them a dignified workplace.